Perceived Stress, Subjective, and Objective Symptoms of Disturbed Sleep in Men and Women with Stable Heart Failure. Issue 3 (4th May 2021) - Gaffey, Allison E.; Jeon, Sangchoon; Conley, Samantha; Jacoby, Daniel; Ash, Garrett I.; Yaggi, Henry K.; O'Connell, Meghan; Linsky, Sarah J.; Redeker, Nancy S.
ABSTRACT: Objective/Background : Sleep disturbance is prevalent among patients with heart failure (HF) and is associated with increased morbidity and mortality. Stress also affects health and quality of life among patients with cardiovascular disease and likely plays a prominent role in HF. However, little is known about the associations between stress and sleep among HF patients. Participants : One hundred fifty-three stable New York Heart Association (NYHA) Classification I–IV HF patients with at least low symptoms of insomnia (Mage :63.0 ± 12.8, 42% Women). Methods: We examined baseline stress, sleep disturbance, and sleep-related characteristics from a randomized controlled trial of cognitive behavioral therapy for insomnia, including the Perceived Stress Scale, Insomnia Severity Index, Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale, Sleep Disturbance Questionnaire, Dysfunctional Beliefs about Sleep Scale, PROMIS Cognitive Ability, SF-36 Mental Health, and wrist actigraphy. We used Pearson correlations and general linear models to assess stress-sleep associations, including the potential moderating effects of sex and symptom severity (NYHA). Results : There were moderate-to-large correlations between stress and self-reported sleep disturbance, dysfunctional beliefs about sleep, cognitive ability, and mental health ( p 's < 0.01). High stress was associated with more objectively-measured (i.e., actigraph-assessed) awakenings and sleep fragmentation among women than men ( β = − 0.04, p < 0.01; β = − 0.71, p = 0.04). Relationships between stress and objectively-measured sleep did not vary by symptom severity. Conclusions : Perceived stress is related to sleep disturbance among HF patients, and effects may be sex-dependent. Subsequent research should determine the temporal links between sleep and stress, and optimal opportunities for intervention among HF patients.